Adverse selection and credit certificates: Evidence from a P2P platform - Maggie Rong Hu; Xiaoyang Li; Yang Shi (Asian Development Bank Institute (ADBI), 2019)
Certificates are widely used as a signaling mechanism to mitigate adverse selection when information is asymmetric. To reduce information asymmetry between lenders and borrowers, Chinese peer-to-peer (P2P) lending platforms encourage borrowers to obtain various kinds of credit certificates. As P2P markets continue to develop, it is plausible that certification may play a pivotal role in ensuring investment efficiency. We perform the first empirical investigation of this issue, using unique data from Renrendai, one of the People's Republic of China's largest P2P lending platforms. We find that surprisingly, loans with more credit certificates experience a higher rate of delinquency and default. However, lenders remain attracted by higher certificates despite lower loan performance ex post, which results in distorted capital allocation and reduced investment inefficiency. Overall, we document a setting where credit certificates fail to serve as an accurate signal due to their costless nature, where poor-quality borrowers use more certificates to boost their credit profiles and improve their funding success. Possible explanations for this phenomenon include differences in marginal benefit of certificates for different borrower types, bounded rationality, cognitive simplification, and borrower myopia.
Keywords: G10; G20; G21; G23; G40; 330; P2P lending; credit allocation; adverse selection; certificate; bounded rationality; cognitive simplification